Prevalensi Penyakit Karang di Pulau Menjangan Besar Karimunjawa - Nining Nursalim; Agus Trianto; Muhammad Syaifudien Bahry; Dwi Haryanti; Raden Ario; Raja Aditia Sahala Siagian; Akhmad Tri Prasetyo (Jurnal Kelautan Tropis, 2022)
Coral disease can cause coral damage on Menjangan Besar Island, Karimunjawa. Floating net cages adjacent to coral reefs can affect coral health. Floating net cages can affect water quality by adding nutrients, such as nitrate (205.6 and phosphate 39.2/ton fish production). Nutrients and environmental factors can trigger and cause coral disease. The purpose of this study was to determine the effect of the existence of floating net cages on the prevalence of coral disease on Menjangan Besar Island, Karimunjawa. The research was conducted using a survey method, data collection using a proportional method, the results of the data will be analyzed descriptively. The results of the study found Black Band Disease, Brown Band Disease, Ulcerative White Pox, White syndrome, Yellow Bloch Disease, Pigmentation responses, White Plague and White Band Disease. Water parameters such as temperature ranged from 30.71-30.750C, salinity 32.7-33.20/00, current velocity 0.03-0.06 m/s, nitrate 0.586-1,128 mg/L and phosphate 0.064-0.133 mg/ L. The most common disease is Ulcerative White Pox. The prevalence of coral disease is influenced by the presence of floating net cages, it can be seen in A1, A2 and A3 with prevalence values (39.85, 43.61 and 33.14) which are higher than B1 and B2 (14.41 and 10,6).  Penyakit karang dapat menyebabkan kerusakan karang di Pulau Menjangan Besar Karimunjawa. Karamba jaring apung yang berdampingan dengan terumbu karang dapat mempengaruhi kesehatan karang. Karamba jaring apung dapat mempengaruhi kualitas air dengan menambah nutrien, seperti Nitrat (205,6 dan fosfat 39,2/ton produksi ikan. Nutrien dan faktor lingkungan dapat menjadi pemicu dan penyebab penyakit karang. Tujuan penelitian ini untuk mengetahui pengaruh keberadaan karamba jaring apung terhadap prevelensi penyakit karang di Pulau Menjangan Besar Karimunjawa. Penelitian dilakukan dengan metode survei, pengambilan data dengan metode porposif, hasil data akan disanalisis secara deskiptif. Hasil penelitian ditemukan penyakit Black Band Disease, Brown Band Disease, Ulcerative White Pox, White syndrome, Yellow Bloch Disease, Pigmentation responses, White Plague dan White Band Disease. Parameter perairan  seperti temperatur berkisar 30,71-30,750C, salinitas 32,7-33,20/00, kecepatan arus 0,03-0,06 m/s, nitrat  0,586-1,128 mg/L dan fosfat 0,064-0,133 mg/L. Penyakit paling banyak ditemukan adalah Ulcerative White Pox. Prevelensi penyakit karang dipengaruhi oleh keberadaan karamba jaring apung, dapat terlihat pada A1, A2 dan A3 dengan nilai prevalensi (39,85, 43,61 dan 33,14) yang lebih tinggi jika dibandingkan dengan B1 dan B2 (14,41 dan 10,6).